PENYULUHAN PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI SEKOLAH MENENGAH ATAS NEGERI 3 PANGGARANGAN DESA CIMANDIRI KECAMATAN PANGGARANGAN KABUPATEN LEBAK - Teguh Aris Munandar; Febri Saefulloh (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Schools are a foundational institution in building a nation's future. As centers of learning and character development, schools hold a dual role: not only to transfer knowledge but also to foster a safe, inclusive, and equitable environment for all students. In Lebak Regency, Banten Province, sexual violence has emerged as a critical issue demanding urgent attention. Data from various institutions reveal an alarming trend: cases of sexual violence, particularly affecting students, are increasing annually. This phenomenon represents a tangible crisis that threatens the safety and future of the region's younger generation. An educational outreach program on the Prevention and Handling of Sexual Violence was conducted at SMAN 3 Pangarangan (Pangarangan 3 State Senior High School), Cimandiri Village, Pangarangan District, Lebak Regency. This program was designed to provide students with a comprehensive understanding of the topic, aiming to enhance their capacity for self-protection against sexual violence in their daily lives, particularly within the school environment. The program's methodology included lectures, interactive discussions, practical self-protection exercises, and a final evaluation quiz. The program was deemed successful, evidenced by the students' positive feedback and their expressed commitment to implementing the principles of sexual violence prevention and handling.Keywords: Educational Outreach; Prevention and Handling of Sexual Violence; Senior High School.